Strategi Transformasi Agropreneur Muda dalam Perspektif Pertanian Berkelanjutan - Sari, I. Rani Mellya; Syafani, Tyas Sekartiara (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The regeneration of farmers in Indonesia remains slow, with young farmers (<35 years) accounting for only 12.87 percent, while the proportion of elderly farmers continues to increase. This condition reflects the low interest and motivation of young generations to engage in agricultural entrepreneurship. The transformation of young agropreneurs is therefore essential to strengthen farmer regeneration and the competitiveness of farming enterprises amid the challenges of climate change, commodity price fluctuations, and the dynamics of digital markets. This study aims to formulate a strategic model for transforming young agropreneurs oriented toward sustainable agriculture. The research was conducted in South Lampung Regency involving 30 young farmer respondents. A descriptive quantitative and qualitative approach was applied through surveys, in-depth interviews, field observations, and Focus Group Discussions (FGDs). SWOT analysis was employed to identify strengths, weaknesses, opportunities, and threats in the transformation process of young agropreneurs. The findings indicate that young agropreneurs occupy an adaptive diversification strategy position, characterized by stronger internal capabilities than weaknesses. The formulated model emphasizes digital capacity enhancement, product innovation, and institutional collaboration to expand market access and strengthen farm resilience. The model is oriented toward three dimensions of sustainability: economic (efficiency and value addition), social (network and capacity strengthening among young farmers), and environmental (climate adaptation through eco-friendly technologies). This study highlights the importance of synergy among policies, institutions, and human resource development to accelerate the transformation of young agropreneurs toward an innovative, resilient, and sustainable agricultural system.